Galaxies and their Masks A Conference in Honour of K.C. Freeman, FRS - Block, David L.; Freeman, Kenneth C.; Puerari, Ivânio; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Various kinds of masks obscure our view of our galaxy, the Milky Way, as well as of other galaxies. Masks of interstellar dust affect our measurements within galaxies, on scales ranging from individual supernovae to the galaxies themselves. The “mass mask” (our inability to image mass rather than light) gives astronomers a very incomplete picture of the size and structure of galaxies themselves, because we cannot image the dark matter which provides most of the galactic mass. Another mass is the “dynamical mask”: as galaxies form, much dynamical information is lost in the birthing process. A new thrust in research is to retrieve such information by means of chemical tagging. About 50 astronomers flew into Namibia in April 2010, to celebrate the 70th birthday of Professor K.C. Freeman, Fellow of the Royal Society. At age 70, Freeman, a father of dark matter in galaxies, continues to be one of planet’s most highly cited astronomers. The current volume affords readers a unique perspective on galaxies by probing the thoughts of some of the greatest astronomers of our age. Contributions focus on galaxies from within our Local Group to those in our high redshift Universe. Approximately 40 in-depth review and contributed papers are contained in the volume, each written by an expert in the field. Two unusual features of the current volume include the “Star Country” of the San people of southern Africa as well as the introduction into astronomy of “The Treachery of Images” by the Belgian surrealist artist René Magritte. “Everything we see hides another thing, we always want to see what is hidden by what we see”, said Magritte. These words resonate the theme of the current volume “Galaxies and their Masks”, which is written at a level to be appreciated by both specialist and doctoral student alike.
Stars are Small Dark-Coloured Things That Live in Holes in the Ground -- Shrouds of the Night – Galaxies and René Magritte -- Twin Masks of Spiral Structure? A Local Perspective -- The Mask of Complexity in Disk Galaxies -- Cosmic Magnetic Fields – An Overview -- The Gaseous Halo Mask -- Molecular Gas Properties of Galaxies: The SMA CO(2-1) B0DEGA Legacy Project -- The DiVA’s Mask: Iconifying Galaxies and Revealing HI Anomalies -- Enigmatic Masks of Cosmic Dust: Lessons from Nearby Galaxies Through the Eyes of the Spitzer Space Telescope -- The Large Magellanic Cloud: A Power Spectral Analysis of Spitzer Images -- Light Cores Behind Dark Masks -- Globalization, Open Access Publishing, and the Disappearance of Print: Threat or Opportunity? -- Super Star Clusters and Supernovae in Interacting LIRGs Unmasked by NIR Adaptive Optics -- Structure, Mass, and Stability of Galactic Disks -- What Can the Radial Surface Brightness Profiles of Galaxy Discs Tell Us About Their Evolution? -- The Complex Interplay of Dust and Star Light in Spiral Galaxy Discs -- Galaxy Morphology Revealed By SDSS: Blue Elliptical Galaxies -- Rings and Bars: Unmasking Secular Evolution of Galaxies -- Bars and Bulges Through Masks of Time -- Tidal Trails and Mass-Segregated Isothermal Clusters -- Stellar Debris Streams: New Probes of Galactic Structure and Formation -- Chemical Enrichment in Galaxies: Constraints on Nucleogenesis and Galaxy Evolution -- Chemodynamical Simulations of Galaxies -- Elemental Abundance Patterns of Disk Substructure -- Searching for Structures and Streams in the Extended Solar Neighbourhood with RAVE -- On the Age–Metallicity–Velocity Relation in the Nearby Disk Using the RAVE Survey -- The HERMES Project: Reconstructing Galaxy Formation -- Stellar Halos: Unmasking a Galaxy’s History -- The Outer Halos of Elliptical Galaxies -- Galaxies: Lighthouses in the Shoals of Dark Halos -- Dark Haloes as Seen with Gravitational Lensing -- Behind the Mask: Resolving the Core–Cusp Problem in Spiral Galaxies -- A GALAXY BASELINE: Multiwavelength Study of a Sample of the Most Isolated Galaxies in the Local Universe -- Diffuse Light and Galaxy Interactions in the Core of Nearby Clusters -- Feedback in Star and Galaxy Formation -- When Bad Masks Turn Good -- Spitzer’s View of Galaxies in the High-Redshift Universe -- Bandshifting and Other Masks of the Clumpy Populations in High-Redshift Galaxies -- Supernovae, Dust, and Cosmology.
Keywords: Space sciences; Observations, Astronomical; Astronomy—Observations.; Space Sciences (including Extraterrestrial Physics, Space Exploration and Astronautics).; Astronomy, Observations and Techniques